Enzyme Immobilization on Maghemite Nanoparticles with Improved Catalytic Activity: An Electrochemical Study for Xanthine - Magro, Massimiliano; Baratella, Davide; Venerando, Andrea; Nalotto, Giulia; Basso, Caroline R; Molinari, Simone; Salviulo, Gabriella; Ugolotti, Juri; Pedrosa, Valber A; Vianello, Fabio (Materials (Basel, Switzerland), 2020)
Generally, enzyme immobilization on nanoparticles leads to nano-conjugates presenting partially preserved, or even absent, biological properties. Notwithstanding, recent research demonstrated that the coupling to nanomaterials can improve the activity of immobilized enzymes. Herein, xanthine oxidase (XO) was immobilized by self-assembly on peculiar naked iron oxide nanoparticles (surface active maghemite nanoparticles, SAMNs). The catalytic activity of the nanostructured conjugate (SAMN@XO) was assessed by optical spectroscopy and compared to the parent enzyme. SAMN@XO revealed improved catalytic features with respect to the parent enzyme and was applied for the electrochemical studies of xanthine. The present example supports the nascent knowledge concerning protein conjugation to nanoparticle as a means for the modulation of biological activity.
Keywords: catalytic properties; xanthine oxidases; metal nanoparticles; enzyme immobilization